THE EFFECT OF CIGARETTES ON RED BLOOD CELLS IN ACTIVE TEENAGE SMOKERS IN LEKOBALO VILLAGE, KOTA BARAT DISTRICT - Laras Puspita Taib; Parhan Hanuna (LPPM Universitas Bina Mandiri Gorontalo, 2025)
Cigarette smoking during adolescence may affect hematological function through exposure to carbon monoxide, oxidative compounds, and other tobacco-related toxicants. This study aimed to determine the association between cigarette smoking frequency and red blood cell (RBC) values among active adolescent smokers in Lekobalo Village, Kota Barat District. A quantitative analytical observational study with a cross-sectional design was conducted in September 2025. The study involved 30 active smokers aged 15–19 years who consumed 3–10 cigarettes per day and were selected using random sampling. Smoking frequency was assessed through self-reported daily cigarette consumption, while RBC values were determined through laboratory examination of venous blood samples. Descriptive statistics and inferential analysis were performed, with statistical significance set at p < 0.05. Participants reported a mean smoking frequency of 6.13 ± 2.193 cigarettes per day, while the mean RBC concentration was 4.2020 ± 0.29847 million/µL, with values ranging from 3.70 to 4.76 million/µL. Inferential analysis demonstrated a statistically significant association between smoking frequency and RBC examination results (F = 11.623, p < 0.001). These findings indicate that variation in cigarette consumption was associated with variation in RBC values among adolescent smokers. However, the cross-sectional design does not establish a causal relationship. Early smoking prevention, cessation counseling, and appropriate hematological monitoring should be strengthened to reduce potential biological consequences of tobacco exposure among adolescents.